The Power of Speech by Medicine Vendor - Musfirah Musfirah (Universitas Cokroaminoto Palopo, 2018)
The speech of medicine vendor contains power to convince the costumers. This study is aimed at investigating the linguistics features used in the in the speech of medicine vendor. This study is descriptive qualitative in analyzing and displaying the data. The techniques of analyzing data were transcribing the utterances, translation the data into English by applying morpheme by morpheme translation and idiomatic translation, and identifying the linguistics features of medicine vendors’ speech. The result of this study revealed that parallelism is one of the linguistics features used in the speech to build a power.